2007
DOI: 10.2166/wst.2007.442
|View full text |Cite
|
Sign up to set email alerts
|

Sorption behaviour of oxadiazon in tropical rice soils

Abstract: The soprtion behaviour of a pre-emergent herbicide, oxadiazon (5-tert-butyl-3-(2,4-dichloro-5-isopropoxyphenyl)-1,3,4-oxadiazol-2 (3H)-one) was investigated in tropical rice soils using a batch equilibrium method. There is no information available on the fate of oxadiazon in Bangladeshi soils; Bangladesh rice soil is a unique environment. The experiment was performed using radiolabelled (14C) oxadiazon. The sorption and desorption isotherm of oxadiazon was described using the Freundlich equation. L-type sorpti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 11 publications
1
6
0
Order By: Relevance
“…As already reported by Hoque et al (2007), the oxadiazon sorption by the soil is a rapid process and linearly related to the concentration, depending on the OC content and occurs within two hours.…”
Section: Resultssupporting
confidence: 67%
“…As already reported by Hoque et al (2007), the oxadiazon sorption by the soil is a rapid process and linearly related to the concentration, depending on the OC content and occurs within two hours.…”
Section: Resultssupporting
confidence: 67%
“…In general, the lower the solubility of a certain compound, the higher its adsorption [22]. It has been found that soil organic content was the primary factor in oxadiazon adsorption [22,23]. According to Wehtje et al [6], adsorption of oxadiazon in different substrate types was at least 96%.…”
Section: Discussionmentioning
confidence: 99%
“…The authors postulated that these differences were due to the agronomic practices adopted in the second year on lettuce, and in particular, to the frequent irrigations carried out over the season [25]. Despite the low degradation, this herbicide is generally considered with a reduced risk of leaching [4,23,24] and the losses by volatilization are negligible due to its low vapor pressure [2,4,24].…”
Section: Discussionmentioning
confidence: 99%
“…Other two pesticides from the 1st WL, that is, oxadiazon and tri‐allate, are selective pre‐emergence herbicides. Oxadiazon belongs to the chemical class of oxadiazoles, largely used in rice crops against both mono and dicotyledonous weeds . Tri‐allate (thiocarbamate chemical class) is widely used to control annual and perennial grasses.…”
Section: Characteristics Of the Pesticides From The Eu First And Secomentioning
confidence: 99%
“…Oxadiazon belongs to the chemical class of oxadiazoles, largely used in rice crops against both mono and dicotyledonous weeds. [66] Tri-allate (thiocarbamate chemical class) is widely used to control annual and perennial grasses. Both were included in the 1st WL because of the apparently very high RQ.…”
Section: Metaflumizone Methiocarb Oxadiazon and Tri-allatementioning
confidence: 99%